Effect of orally administered l-glutamine on gene expression of the humoral immune response of the intestinal mucosa of baby alpaca (Vicugna pacos) - Bejarano L., Emanuel (2017)
This study aimed to determine the effect of L-glutamine on the expression of immunoglobulin A (IgA) and cytokines TGF-β and interleukins IL-4, IL-5, IL-6 and IL-10 in the mucosa of the jejunum of 4-7 days old alpacas. A group of 6 alpacas was orally administered 3.3 mM L-glutamine per kg body weight and a second dose 7 days later. A second group of 7 alpacas received PBS as control. All animals were euthanized 3 days after the treatment and a portion of the jejunum was collected. The messenger RNA (mRNA) was extracted and the reverse transcription (RT) and real-time PCR was done using primers specific for each gene in study. The 2-ΔΔct method was used for the relative quantitation of IgA, TGF-β and interleukins. The TGF-β expressed 3 times more and IgA 18 times more in alpacas treated with L-glutamine than in the controls (p<0.05). The expressions of IL-4, IL-5, IL-6 and IL-10 showed similar levels in the treated and control animals. It is concluded that L-glutamine increases the expression of TGF-β and IgA improving the humoral adaptive immune response of intestinal mucosa in new-born alpacas.